Anti‐inflammatory effects of bamboo salt and sodium fluoride in human gingival fibroblasts–An in vitro study. Issue 6 (27th April 2015) - Lee, Hye‐Jin; Choi, Choong‐Ho
Abstract: Dental caries preventive agents, such as sodium fluoride (NaF) and bamboo salt (BS), are known to cause cellular growth that is characterized by morphological and gene expression changes. This study was designed to investigate the dual effect of NaF and BS on interleukin (IL)‐1β‐induced gingival inflammation. Under in vitro experimental conditions, exposure to a subcytotoxic dose of IL‐1β enhanced human gingival fibroblast inflammation, as characterized by increased levels of inflammation‐associated proteins. A combination of NaF and BS significantly protected fibroblasts from IL‐1β‐induced cellular deterioration. Exposure to NaF and BS induced the cell growth and no changes in viability were found with the Lactate Dehydrogenase Assay (LDH) assay at the NaF and BS concentration analyzed. Molecular analysis demonstrated that NaF and BS increased resistance to inflammation by reduction of IL‐1β, IL‐8, and tumor necrosis factor (TNF)‐α production. In addition, NaF and BS decreased the expression of IL‐1β, IL‐8, and TNF‐α mRNA in IL‐1β‐induced human gingival fibroblast cells. The study identifies a new role for NaF and BS in the IL‐1β‐induced inflammation of gingival fibroblasts and provides a potential target for gingival protection.